The contribution of interregional and inter-field knowledge spillovers to regional Smart Specialisation. Issue 2 (1st February 2023) - Wu, Haixiao
ABSTRACT: Industrial policy based on Smart Specialisation emphasizes the exploitation of industrial linkages based on technological rather than intermediate product linkages. This paper develops microlevel analysis using the Organisation for Economic Co-operation and Development's (OECD) patent citation database on the intensity of technical relatedness depending on the cited and citing technological fields. The results are used to estimate the patterns of interregional knowledge spillovers in the European Union and explain spatial differences in patent growth. The approach to identifying spillovers provides an improved toolbox to guide implementation of Smart Specialisation policies.